Design and shape control technology of asymmetric universal crown temper mill. (7th February 2016) - Bai, Z. H.; Guo, Q. Y.; Xing, Y.; Qian, C.; Liu, Y. X.; Wang, R.; Li, J. Z.
Abstract : The conventional universal crown mill (UCM) temper mill cannot be controlled well for asymmetric high-order complex wave shapes; thus, a novel type of asymmetric universal crown temper mill (AS-UCM) was designed, which was configured for asymmetric bending of the work roll and intermediate roll, as well as asymmetric axial shifting of the intermediate roll. The corresponding shape control technology was established. Taking the typical production process as an example, the present study quantitatively analysed the control effect of AS-UCM and the ordinary UCM temper mill on asymmetric high-order complex wave shapes. Moreover, the related technology was commercially applied to the 750 mm AS-UCM with great economic benefits.